Mitochondrial Dynamics: Functional Link with Apoptosis - Hidenori Otera; Katsuyoshi Mihara (International Journal of Cell Biology)
Mitochondria participate in a variety of physiologic processes, such as ATP production, lipid metabolism, iron-sulfur cluster biogenesis, and calcium buffering. The morphology of mitochondria changes dynamically due to their frequent fusion and division in response to cellular conditions, and these dynamics are an important constituent of apoptosis. The discovery of large GTPase family proteins that regulate mitochondrial dynamics, together with novel insights into the role of mitochondrial fusion and fission in apoptosis, has provided important clues to understanding the molecular mechanisms of cellular apoptosis. In this paper, we briefly summarize current knowledge of the role of mitochondrial dynamics in apoptosis and cell pathophysiology in mammalian cells.